Hemorrhagic transformation in patients with ischemic stroke and atrial fibrillation: to anticoagulate or not, that is the question - Vasconcelos, Tiago (2024)
The management of anticoagulation in patients with ischemic stroke and atrial fibrillation (AF) poses a critical dilemma due to the inherent risk of hemorrhagic transformation. This article presents the case of an 89-year-old male with AF and recurrent ischemic strokes, highlighting the complex challenge of deciding whether to initiate or withhold anticoagulation. After the initial ischemic stroke event, the patient started a direct oral anticoagulant. Subsequent imaging revealed hemorrhagic transformation, leading to the cessation of anticoagulation. Despite multiple hemorrhagic recurrences, balancing thrombotic and bleeding risks remained challenging. Mechanical thrombectomy was performed for a subsequent ischemic stroke due to an absolute contraindication for thrombolysis. The patient's intricate clinical course involved a multidisciplinary approach, resulting in a decision to cautiously resume low-dose anticoagulation combined with left atrial appendage closure. This decision was made after careful consideration of persistent thrombotic risk despite recurrent hemorrhages. The case underscores the complex management dilemma of anticoagulation in elderly patients with AF and recurrent strokes, emphasizing the need for a multidisciplinary approach and individualized decision-making in such challenging scenarios. Further research and guidelines are warranted to establish optimal strategies for (re)initiating anticoagulation in patients with recurrent hemorrhagic transformation.